Is there a Virtual Personality? A psycholexical informed exploratory Study of Personality Traits in Virtual Environments in Spanish-speaking population - Castro Solano, Alejandro (2025)
The aim of this research was to explore the concept of virtual personality. Traditional personality models were developed based on characteristics of the real (or offline) world. Given the evidence suggesting that people may behave differently in virtual environments, it is important to explore whether there is a virtual way of being: a virtual personality. To address this objective, three consecutive studies were conducted using various samples of Spanish-speaking adults from the general population. In Study 1, a list of adjectives that people reported using to describe how they and others are in virtual environments was developed. In Study 2, the list was psychometrically analyzed to generate both a theoretical model and a measurement instrument. A three-factor/traits model was obtained: authenticity, cautiousness, and agreeableness and sociability. The virtual personality model was named ACAS. In Study 3, its associations with normal traits and its predictive power over internet related behaviors were analyzed. ACAS’ traits are related to normal personality traits but do not constitute the same construct and present incremental validity when predicting internet related behaviors. This virtual personality model constitutes an initial approach and should be studied in greater depth in other samples and in longitudinal studies that analyze its temporal stability.